Analysis of purchasing decisions through advertising on social media, product completeness and brand image on the Tokopedia application - Sumadi Saputra; Muinah Fadhilah; Agus Dwi Cahya (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research aims to determine the influence of